Optimalisasi Peran Masjid sebagai Pusat Pendidikan Non Formal dalam Perkembangan Umat Muslim - Endah Tri Wahyuningsih (STAI Terpadu Yogyakarta, 2022)
The massive construction of mosques that are comfortable and easily accessible in society in the current era is an interesting phenomenon to generate enthusiasm for acquiring knowledge for the development of Muslims. The mosque in the context of the physical environment as a means of non-formal education has an optimal role. This study analyzes how to optimize the role of the mosque as a center for non-formal education in the development of Muslims. The research was conducted using a qualitative descriptive method with the type of literature research. From this research, it was found that optimizing the role of the mosque in the scope of non-formal education means managing the organizations within the institution well so as to produce the development of Muslims as seen from the output of the quality of humans who have extensive knowledge of the Islamic religion and are able to apply it in life based on Al Quran and As Sunnah as well as the understanding of the Companions. Optimizing the role of the mosque will indirectly support the development of Muslims as whole human beings, especially children as the next generation. Optimizing the role of mosques aims to enable mosques to support development programs for Muslims universally.Managing mosques in optimizing their role for non-formal education through routine activities in mosques, namely through educational activities such as 1) Mosque Schools, a teaching and learning program in which the curriculum is delivered specifically regarding religious materials to assist formal education. 2) Halaqoh (study circle) led by a scholar with the main material on Islamic religious knowledge with its various branches. 3) The Reading Literacy through the mosque's library which provides readings of Islamic sources and 4) Scientific I'tikaf, a discussion room used for discussions before and after congregational prayers.